Landholders’ perceptions on legal reserves and agricultural intensification: Diversity and implications for forest conservation in the eastern Brazilian Amazon - Pinillos, Daniel (2021)
Forest conservation on privately owned lands is a cornerstone of the Brazilian environmental policy framework. Brazilian legislation requires that all farms in the country maintain and protect forest areas known as Legal Reserves. Since Legal Reserves have major implications for forest conservation and agricultural production, it is key that we understand landholders’ perceptions towards Legal Reserves. We applied Q methodology to identify different perspectives of medium and large landholders on Legal Reserves and their relation to agricultural intensification in the municipality of Paragominas, eastern Amazon. We conducted 31 interviews in which landholders sorted 36 statements in a quasi-normal distribution array. Three groups of landholders were identified: 1) Land use planning enthusiasts (n = 16) were interested in zoning initiatives to explore alternative landscape designs and legislation that may deliver better conservation and production outcomes; 2) Agrochemical-based agriculture supporters (n = 7) held the most critical views against Legal Reserves and perceived their costs as higher than the potential environmental and life quality benefits; 3) Policy complacentmarket responders (n = 4) showed no interest in Legal Reserves reforms and were the most market driven group.. While Paragominas has achieved notable successes in halting large-scale deforestation through a social “Green Municipality” pact, addressing persisting forest degradation and fragmentation in the region remains a key priority. Local governance initiatives that account for multi-stakeholder perceptions on forest conservation can foster dialogue and mutual understanding to effectively conserve and restore Legal Reserves. Insights on large landholders’ perceptions on Legal Reserves can inform such governance processes to reconcile forest conservation and sustainable agricultural intensification in Paragominas.